The role of Waqf for mitigating adaptation barriers for Malaysian rice farmers - Afroz, Rafia; Fauzi, Puteri Farhana; Khalid, Haniza (2016)
Malaysia is one of the newly growing industrializing countries. In the path of economic development from agriculture to industrial movement, the agricultural sector in Malaysia has contributed significantly to the gross domestic product (GDP). This research is intended to connect the potential of agricultural production and direct them to contribute to the Malaysian economy. However, the contribution of agriculture has been declining as 8.9% in 2000 and 8.2% in 2005. Because farmers in Malaysia has to face a number of barriers to adaptation, such as financial, human. Capital. Physical, and especially natural barriers due to climate change. To overcome the situation, we need to find alternative solutions. The aim of this study is to propose an integrated waqf environmental protection model .The proposed model can be one of the options that are expected to help affected farmers to mitigate barriers. This study will help policy makers to plan more effective policies to improve the potential role of waqf to mitigate barriers to adaptation and sustainable livelihoods of rice farmers in Malaysia. While the author's knowledge, the idea of environmental waqf is a relatively new concept and today certainly need a lot of discussion.